INTERPRETATION OF SYNONYMY IN UZBEK LINGUISTICS - Gaffarjon Rozmatovich Rahmonov (Journals Park Publishing, 2023)
The present paperconsiders the traditional and contemporary views on defining synonyms in Uzbek linguistics, wheredistinguishing the similarities and differences in semic analyses of the lexical meanings of synonyms worth special attention.
Keywords: lexical synonymy, lexical meaning, semic analyses, differences of meaning, stylistic features, conotation, emotional shade, dominance, neutral word, semantic phenomenon, semasiological bases, semantic structure of the word, sememe, seme, nomeme, similarity, difference, commoness.